Analisis Efektivitas Sistem Pengendalian Internal Dalam Mengatasi Kredit Macet Dengan Menerapkan Prinsip â€œPang Pade Payuâ€ Pada BUMDES Sidi Amerta - Erawati, Made; Atmadja, Anantawikrama Tungga (Universitas Pendidikan Ganesha, 2020)
BUMDes Sidi Amerta is an official institution with a village managed by a joint and legal entity village, one of the operations of which is a savings and loan business. This study was intended to find out (1) How the internal control system applied by the Sidi Amerta Village Business Entity in implementing bad credit, (2) How to apply the